Comparison of perinatal outcome in twin pregnancy with and without cervical cerclage - Chavan, Mitesh Suresh; Jassawalla, Mehernosh Jamshed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The incidence of multifetal pregnancies has registered increase globally. Babies born from multiple-birth pregnancies are much more likely to result in premature birth than those from single pregnancies. Knowledge of role of cervical cerclage in preventing preterm birth especially in twin pregnancy can be helpful to prevent complication related to preterm birth and ultimately of low birth weight babies. Methods: Depending upon who opt for the procedure 100 patients were divided equally into two groups: 1)Twin pregnancy with cervical cerclage; 2)Twin pregnancy without cervical cerclage. We measured maternal outcomes which include time for which patient required to be hospitalized, maternal pyrexia, cervical or bladder injury and other maternal morbidity and perinatal outcomes which include preterm delivery (delivery before 37 completed weeks), low birth weight (birth weight ≤2000 g), IUGR, perinatal mortality, indicators of perinatal morbidity (APGAR scores and neonatal unit admission), stillbirth, second trimester loss and presence of congenital malformations. Results: In Study group 22% delivered before 34 weeks of gestation, 46% delivered between 34 and 37 weeks of gestation, 32% delivered after 37 weeks of gestation compared to 44%, 48% and 8% respectively in Control group. The mean gestational age at delivery was 35.3 weeks in Study group and was 33.2 weeks in Control group. In study group 47% neonates had birth weight less than 2Kg and in Control group 69% neonates had birth weight less than 2Kg. In Study group 95% had Apgar score more than 6 whereas in Control group 86% had APGAR score more than 6. The mean APGAR for Study group was 8.5 and for Control group was 7.5. 45% neonates had complications in Study group whereas 67% neonates in Control group. Overall Low birth weight was most common complications in both the groups. Respiratory distress was more common in Control group. Conclusions: In spite of close vigilance, preterm birth in twin gestation is common and unpredictable. It is difficult to predict those who may require cervical cerclage although all multiple pregnancies are at high risk. Cerclage should be considered an option for patients with twin pregnancies in the second trimester to prolong the duration of gestation as close to term as possible.